Frequency of Anemia Associated with Maternal Factors in Pregnancy - Parus Saleem, Atta Muhammad Chandio, Jawaid Hussain Lighari, Noor Ali Samoan, Riaz Ahmed Mangi , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2017)
Objectives: To determine the frequency and maternal risk factors associated with anemia in pregnancy in Nawabshah (SBA). Methods: A community based cross-sectional study conducted in eight Union Councils of Nawabshah City District Shaheed Benazirabad from April 2016 to October 2016. Total 372 pregnant women from Nawabshah City were enrolled by simple random probability sampling. All were interviewed regarding parity, trimester or stage of pregnancy and birth spacing (family planning). Their blood sample was taken by aseptic measures. The blood samples were sent to Diagnostic Laboratory PUMHS Nawabshah (SBA) for Hemoglobin estimation (Hb%). Data was entered and analyzed by SP SS Software. Result: 69.1 % population of pregnant women were anemic among which 26.8% have mild, 47.4% have moderate and 25.6% have severe anemia.76.5% of pregnant women in first trimester were anemic, while 62% ofpregnant women in third trimester. 71.4% ofpregnant women with birth spacing less than 2 years were anemic, while 63.7% of pregnant women with birth spacing more than 2 years were anemic. 70.6% of prim-gravida women were anemic, among which 25.3% have mild, 46.2% have moderate and 28.3% have severe anemia. 67.3% of multigravida were anemic among which 27.2% have mild, 48.4% have moderate and 24.2% have severe anemia. Conclusion: Maternal factors like parity, stage of pregnancy and birth spacing play vital role in prevalence of anemia in turn on the health status ofboth mothers and newborns.